Gains from Targeting? Government Subsidies and Firm Performance in China - Jiuli Huang; Yabin Wang; Min Zhu (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2025)
This paper studies the firm-level impact of the world's largest targeted capital import subsidy program implemented in China. Drawing on rich manufacturing firm survey data, product-level trade transactions, and a comprehensive list of capital goods eligible for subsidies, we exploit variation in firms' exposure to the subsidy program to assess its impact on credit access, investment, sales, and trade. We find that a one-standard-deviation increase in a firm's exposure to the subsidy leads to a 0.03% increase in total borrowing and a 0.05% reduction in financing costs. These financial benefits translate into substantial real effects, including a 0.15% rise in investment and a 1.39% improvement in the marginal revenue product of capital. The program's benefits persist over time and are especially pronounced for financially constrained firms and non-state enterprises, indicating that targeted import subsidies can effectively alleviate market frictions and foster industrial development.
Keywords: F13; F14; D22; 330; Government subsidy; credit allocation; investment; financial constraint